On Distinctions Between Lexical Units Denoting a Female Scientist in Czech and Polish: badatelka and badaczka, vědkyně and naukowczyni - Skwarska, Karolína (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article focuses on lexical units denoting a female scientist in Polish and Czech. It draws attention to differences between the two languages, especially at the syntactic and semantic levels (the possibility of expressing the field of specialisation of a female scientist and the form of such an expression), as well as the level of word formation (low frequency of the use of fem. naukowczyni as opposed to masc. naukowiec in Polish, multi-word expressions, etc.). The study is based on the analysis of concordances in text corpora (the Czech National Corpus, including InterCorp, and the National Corpus of Polish) in comparison with the data available in various dictionaries.